Surgery of a Giant Coronary Sinus Aneurysm Resulting from a Coronary Artery Fistula - Diab, Nawras; Barghout, Mohamed; Kueri, Sami; Soschynski, Martin; Siepe, Matthias (The Thoracic and Cardiovascular Surgeon Reports, 2023)
Coronary artery fistula (CAF), complicated by the aneurysmal formation of the coronary sinus (CS), is a very rare form of CAF. Here we report a case of a 60- year-old woman with a giant aneurysm of the CS resulting from the right coronary artery (RCA) fistula. The patient was highly symptomatic with dyspnea due to compression of cardiac chambers. CS reconstruction was performed using a pericardial patch after directly closing the fistula from the RCA to the CS.
Keywords: aneurysm; Coronary Sinus; Fistula